2009
DOI: 10.1111/j.1365-2222.2009.03281.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary periarterial inflammation in fatal asthma

Abstract: Our results show that the adventitial layer of the pulmonary artery participates in the inflammatory process in FA, demonstrating increased infiltration of mast cells, eosinophils, and neutrophils, but not of T and B lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 56 publications
0
26
1
1
Order By: Relevance
“…Post mortem studies have shown that the outer wall of the small airways was a major site of inflammation (especially with eosinophils) [8]. Inflammation in fatal asthma extended to the adjacent alveoli [9] and to the perivascular areas [10]. Studies have also shown loss of alveolar attachments in fatal asthma [11], which positively correlated with both mast cell and eosinophilic inflammation, suggesting roles for these inflammatory cells in alveolar disruption.…”
Section: Pathology Of Small Airways In Asthma and Copdmentioning
confidence: 99%
“…Post mortem studies have shown that the outer wall of the small airways was a major site of inflammation (especially with eosinophils) [8]. Inflammation in fatal asthma extended to the adjacent alveoli [9] and to the perivascular areas [10]. Studies have also shown loss of alveolar attachments in fatal asthma [11], which positively correlated with both mast cell and eosinophilic inflammation, suggesting roles for these inflammatory cells in alveolar disruption.…”
Section: Pathology Of Small Airways In Asthma and Copdmentioning
confidence: 99%
“…Emerging evidence suggests that pulmonary inflammation associated with Th2-mediated inflammation could represent a novel pathway for the pathogenesis of pulmonary arterial remodeling. While the pathology seen in asthma is often described as limited to the airways, pulmonary artery pathology is also found in those with fatal asthma (39). A recent study of asthma patients showed that bronchial arteries exhibited an increase in intimal area, associated with smooth muscle proliferation and calcification of the elastica, and a corresponding decrease in luminal area (16).…”
Section: Discussionmentioning
confidence: 99%
“…A study of asthma patients showed that bronchial arteries exhibited an increase in the intimal area, associated with smooth muscle proliferation and calcification of the elastica, and a corresponding decrease in the luminal area (16). In addition, pulmonary artery pathology has also been found in those with fatal asthma (39). While the pathophysiology of pulmonary arterial remodeling remains largely unclear, recent advances implicate a role for inflammation in the process that results in an imbalance between cellular proliferation and apoptosis, the presence of inflammatory cells in the remodeled artery microenvironment, and an association with increased levels of inflammatory mediators, including various chemokines and cytokines (12,19).…”
mentioning
confidence: 99%
“…In addition, the degree of neutro philic inflammation strongly relates to worsening lung function [201,202]. Finally, in patients who died soon after the onset of a severe asthma exacerbation, autopsies have shown the presence of neutrophils [203][204][205].…”
Section: Neutrophilic Asthmamentioning
confidence: 97%